2006
DOI: 10.1177/1538192705285470
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Baccalaureate Degree

Abstract: The bachelor of applied arts and sciences (BAAS) degree is a baccalaureate program designed to meet the needs of nontraditional students by allowing technical hours to be transferred for credit to a baccalaureate degree. To determine if the university was positively serving the needs of its constituents, salaries of BAAS graduates were compared to salaries of graduates of the academic bachelor of business administration from 1995 to 2000. No statistical difference was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Perceived autonomy support offers choice and options that induce people to think of the future. Arney et al (2006) suggested that the choice of college or a specific major affects a person's future success, as if one may become a successful CEO of a Fortune 500 Company due to the choice he/she makes. Using LinkedIn gives professionals choices and options that encourage them to plan and act on their future career development and advancement.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived autonomy support offers choice and options that induce people to think of the future. Arney et al (2006) suggested that the choice of college or a specific major affects a person's future success, as if one may become a successful CEO of a Fortune 500 Company due to the choice he/she makes. Using LinkedIn gives professionals choices and options that encourage them to plan and act on their future career development and advancement.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative degree programs could be the answer to the conundrum that colleges and universities are facing. Stackable programs, also called applied or workforce degrees or 2+2 degree programs, are designed to add an academic degree component to the technical base in order to meet the needs of graduates of technical colleges (Arney et al, 2006). Stackable degrees allow colleges and universities to cater to the undergraduate populations that are currently growing: nontraditional and underrepresented students.…”
Section: Introductionmentioning
confidence: 99%
“…The other transfer policy that assist student in the transfer of career and technical education degrees is applied baccalaureate. The AB was developed primarily to solve the difficulties in transferring applied associate degree from community college to a baccalaureate serving institutions (Arney et al, 2006).…”
Section: Career Technical Education and Transfermentioning
confidence: 99%
“…The increased importance placed on workforce development, baccalaureate degree attainment, and student transfer prioritized at the state and institutional levels has impacted the development and growth of AB degrees. The AB degree was developed primarily to solve the difficulties in transferring applied associate degrees from a community college to a university (Arney et al, 2006;Townsend et al, 2009;Walker & Floyd, 2005).…”
Section: Applied Baccalaureatementioning
confidence: 99%
See 1 more Smart Citation